1983
DOI: 10.1126/science.6857267
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Cardiac Substances: Potent Vasorelaxant Activity in Mammalian Atria

Abstract: Mammalian atrial extracts possess natriuretic and diuretic activity. In experiments reported here it was found that atrial, but not ventricular, extract also causes relaxation of isolated vascular and nonvascular smooth muscle preparations. The smooth muscle relaxant activity of atrial extract was heat-stable and concentration-dependent and could be destroyed with protease. Rabbit aortic and chick rectum strips were used for the detection of atrial biological activity. The atrial activity was separated by colu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
182
2

Year Published

1984
1984
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 694 publications
(188 citation statements)
references
References 14 publications
4
182
2
Order By: Relevance
“…De Bold et al (32) demonstrated the diuretic effect of atrial extracts and later determined the structure of ANP (33). The myorelaxing action of the atrial extracts on vascular muscle was demonstrated independently by different groups (34)(35)(36). These findings permitted the identification and characterization of hormones of the natriuretic peptide family, which are involved in the control of body fluid homeostasis (36,37).…”
Section: Neurohypophyseal Hormones and The Control Of Sodium And Watementioning
confidence: 99%
“…De Bold et al (32) demonstrated the diuretic effect of atrial extracts and later determined the structure of ANP (33). The myorelaxing action of the atrial extracts on vascular muscle was demonstrated independently by different groups (34)(35)(36). These findings permitted the identification and characterization of hormones of the natriuretic peptide family, which are involved in the control of body fluid homeostasis (36,37).…”
Section: Neurohypophyseal Hormones and The Control Of Sodium And Watementioning
confidence: 99%
“…Various sites of action of ANF have been documented, including arterial muscular tone [8,9], urinary sodium and water excretion [ 10,111, adrenal mineralocorticoid secretion [ 12,131 and pituitary vasopressin secretion [14]. The mode of action of ANF on kidney function is still debated [7].…”
Section: Introductionmentioning
confidence: 99%
“…Atrial natriuretic factor (ANF) has well-known vasorelaxant properties [1]. In particular, we have shown that atriopeptin III (APIII) inhibits angiotensin II (ANGII)-induced contraction of cultured rat glomerular mesangial cells while the shorter fragment atriopeptin I (API) has no such effect [2].…”
Section: Introductionmentioning
confidence: 99%